PEMBELAJARAN MULTIKULTURALISME DALAM PENDIDIKAN ISLAM - Rahimi Rahimi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Multicultural Islamic education is one model of Islamic education learning that is linked to the diversity that exists, whether it's the diversity of religions, ethnicity, languages and so forth. This is done because many of us have met in public schools in one class consisting of various students who are very diverse, there are different religions, ethnicities, languages, ethnicities, and so forth. This paper is intended to find out more about how Multicultural Islamic education, as well as the importance of Multicultural Islamic education, is applied. Data collection is done through the documentation method. Where books are determined as primary data sources and secondary data are collected and selected according to the theme under study. The results of the study show that in multicultural Islamic education is very important to be applied, this is to anticipate the reality of the diversity that exists in society. Where is multicultural Islamic education to be able to help bring about peace or tolerance in the midst of the plurality of society itself.